Peran Asean Dalam Menanggulangi Terorisme di Laut Sebagai Ancaman Terhadap Keamanan Maritim - Alviandini Nanda Fajriah; Emmy Latifah (BELLI AC PACIS, 2018)
This study aims to describe maritime terrorism as a new threat to maritime security in ASEAN. This research is a normative legal research by using content analysis to source data. ASEAN as one of the international organizations that oversees Southeast Asian countries has a mechanism of cooperation among members that can be used as an alternative form of countermeasures against terrorism in Southeast Asia, namely, the ASEAN Counter-terrorism and ASEAN Regional Forum. In this study the authors will identify the mechanism of cooperation at the ASEAN level as a form of cooperation in maritime terrorism.